Photostability and photostabilizing effect of humic acids - M. Mekkaoui; M. Elazzouzi; A. Bouhaouss; M. Ferhat; J. M. Chovelon; P. Meallier (International Journal of Photoenergy)
The photolysis of Humic Acids (HA) extracted from Moroccan soil in water under simulated sunlight method has been studied. The photochemical degradation of HA in concentration (30 mg/L) has been followed by TOC (Total Organic Carbon) and E4/E6 ratio (The E4/E6 value widely used to characterize humic acids is the ratio of absorption intensities at 465 and 665 nm). HA were found photostable after 24 h of irradiation exposure and produce a screen effect on photochemical degradation of TRB (Tribenuron-methyl) and IMAZ (Imazapyr) herbicides.